Some aspects of biological effect of emodin on plants - Kakhanouski, Aliaxandr I.; Yurin, Vladimir M.; Kakhanouskaya, Katsiaryna Yu. (Experimental Biology and Biotechnology, 2021)
Emodin, a secondary metabolite of many plants, has a wide spectrum of biological action on various groups of organisms, but the mechanisms of its action on plants are practically not studied. There is an assumption that emodin plays a certain role in allelopathy, getting into the soil with fallen leaves in the form of glycosides, which break down into emodin aglycones and are stored in the ecosystem. The aim of the study was to establish the effects of emodin on growth processes and its effect on heme-containing enzymes. It was found that emodin has an inhibitory effect on the root system of Allium cepa, and also promotes the activation of catalase activity in the roots. When studying the direct action of emodin on the activity of the catalase enzyme in vitro, it was found that the activity of the catalase enzyme decreases under the action of emodin. When studying the possible mechanisms of inactivation, it was found that emodin can interact with heme. Further detailing of the patterns of biological action of emodin will expand the scope of its application in plant protection, crop production, and also determine its role in plant ecology and physiology.